Resuming Elective Paediatric Surgical Procedures in the Era of COVID-19 - Al-Omar, Khaled (Afr J Paediatr Surg, 2021)
BACKGROUND: The novel coronavirus and the disease it causes COVID-19, like other viral outbreaks, have an unpredictable timeline. Therefore, a triumph in the battle against COVID-19 could only be achieved if a health care system's capacity to support a potentially overwhelming increase in critical patient care needs is maintained, and the viral curve is flattened. Accordingly, health care bodies around the globe called upon prioritising appropriate resource allocation as it relates to elective invasive procedures and minimising the use of essential items required to care for patients. The unpredictability COVID-19 timeline in the absence of effective drug treatments and vaccination along with the restrictive health care policies implemented suggest that patients may be deprived of access to needed surgical care, likely for many months. However, the potential undue delay in delivering essential elective surgical care may have a more detrimental impact on patients’ health compared to that of COVID-19 itself. This particularly applies to the paediatric population in which infection rates have been demonstrated to be considerably lower and mortalities have not been reported yet. Therefore, the need emerges for actions to be taken that allow for the resumption of essential elective surgical procedures in this population of patients. MATERIALS AND METHODS: A comprehensive search through surgical guidance and recommendations to develop a set of evidence based recommendations that allow for the safe and timely delivery of essential paediatric surgical care during the time of COVID-19. CONCLUSION: No compelling evidence that the paediatric population is at an increased risk of morbidity or mortality exists. Therefore, delaying essential paediatric surgical care cannot be justified as it may have a potentially negative health impact, and continuous refinements of surgical recommendations are encouraged in view of evolving circumstances.